Evaluation of Clinical and Immunological Responses: A 2-Year Follow-Up Study in Children with Allergic Rhinitis due to House Dust Mite - Heleen Moed; Roy Gerth van Wijk; Rudi W. Hendriks; J. C. van der Wouden (Hindawi Limited, 2013)
Background. Allergic rhinitis is a disease with polarization towards Th2 and a defect of regulatory T cells. Immunological changes have been reported after immunotherapy treatment. However, there is not much known about the natural course of allergic rhinitis with respect to clinical manifestation and the relation with immunological responses. Objective. To evaluate clinical symptoms of allergic rhinitis, in relation to in vivo allergen-specific skin responses and in vitro allergen-specific effector and regulatory T cells determined at baseline and after two years. Methods. From a large trial, 59 children were randomly selected. The following variables were compared: clinical symptoms, allergen skin tests, specific IgE, T-cell proliferation, IL-5, IL-13, IFN-gamma, IL-10, TGF-beta, CD4+CD25hi cells, and Foxp3 expression. Results. Allergic symptoms had decreased after two years. Whereas skin test reactions correlated between years 0 and 2, there was no change in the size of the reaction. Also, proinflammatory reactions did not change after two years, with a positive correlation between years 0 and 2. No relevant changes were observed with respect to regulatory cells. Conclusion. Whereas, comparable to immunotherapy, allergic complaints decrease, the immunological changes of specific T-cell activity (both effector cells and regulator cells) which are observed after immunotherapy, do not change.